Open land dumping: an analysis of heavy metals concentration of an old Lead-battery dumpsite (2009)
"Use of open land as dump sites by the manufacturing industries in developing countries without appropriate prevention of environmental hazards has resulted in prominent levels of waste and disposal effluents. This has resulted in the contamination of soil and the exposure of human populations to environmental and health hazards. This study focused on the investigation of soil contamination by heavy metals via waste disposal of a lead battery factory in Lalupon, Oyo State, Nigeria. Composite samples obtained from nine sample locations were digested with concentrated acids (HN03, HC104 and HF) and filtered. The filtrate obtained was analyzed for seven different analytes (Cu, Cr, Pb, Zn, Cd, Ni, and As) using atomic absorption spectroscopy (AAS). The lead content exceeded maximum allowable concentrations, MAC (100 ppm), in all points. Copper content was above MAC (50 ppm) in a majority of the points. Cd exceeded MAC (0.3 ppm) in just one point. The study shows that the soil in the old dump site has been contaminated heavily with Pb and Cu. "